Analysis of the communication process from the quality indicators of business institutions in Azerbaijan (Economics and region, 2024)
In modern times, the importance of communication process for organizations plays a vital role, especially with the developments in the world of technology. In a competitive environment, companies need to use corporate communication effectively not only to protect their existence, but also to stand out and be chosen by the target audience. Additionally, to gain an advantage, organizations must place corporate communication at the center of their strategic planning. Companies that prioritize quality workforce in Azerbaijan should take a serious approach to institutionalization in order to increase their productivity and profitability and expand their market shares. While creating institutionalized structures of institutions that must be systematically managed within the framework of certain rules in our country, the success of institutions is ensured by taking a path within the framework of the plan and program. To increase this success and effectively communicate to the target audience, organizations should benefit from corporate communication tools with different characteristics in terms of strategy, form and content. In this article, concepts related to corporate communication, the concept, definition and scope of corporate communication, strategic corporate communication, areas where corporate communication interacts, factors that hinder corporate communication, corporate communication network models, the examination of techniques and tools used in corporate communication, and the research of companies operating in Azerbaijan the degree of importance of the corporate communication process was analyzed in terms of the development of quality indicators of business enterprises.
Keywords: communication process; corporate communication; business enterprises; quality indicators; Azerbaijan